A Technology Transfer Retrospective - Levin, Roy (Computer Systems: Theory, Technology, and Applications, 2004)
Many have written about the challenges that industrial research organizations face in trying to transfer the technology they create to other organizations. Research pursues a long and winding road from the proof of concept of a technology in the lab to the adoption of that technology by others and its use for corporate benefit. To follow the road to its end requires persistence, determination, flexibility, and (when, as is often the case, the road ends short of the destination) good humor. In this short paper, I offer a personal recollection of a part of one such journey — one in which the destination reached wasn’t the one originally sought.